MOHAMMED ARKOUN’S THOUGHT ON METHODOLOGY OF INTERPRETING THE QUR’AN - Syaiful Arief (Al-Dhikra, 2020)
This article explores Arkoun’s thought about Quran and its Interpretation Methodology. In Arkoun’s view, revelation as guidance source for mankind must be treaten not only as sacred thing, but also taken into account that it emerges for mankind benefits. Revelation manifested into muṣḥāf, for Arkoun, must be studied by modern approaches using multidiscipline sciences. So that, we can unravel message substance of revelation maximally. But the most important thing is the unveiling of revelation meaning may not be followed or framed by ideological and political interest or other profane interests, which will reduce revelation become a kind of justification or legitimation. What Arkoun proposes in his interpretation methodology includes approaches as follow: first, Linguistic-Semiotic and Literary Interpretation. By these approaches, he wants to explore the meaning of Quran by explaining every word and syntax arrangement of Quran. Quran consists of sign and symbols that can be analysed semiotically to reach its deepest meaning, and far from ideological point of view. Second, Historical-Antropological Interpretation. This approach acquaints Quran as part of historical life. Then, to understand well the Quran, the interpreter should understand that Quran includes many stories behind the descent. Arkoun recognizes that this method obviously is to challenge all sacralizing and transcendentalizing interpretations produced by traditional theological reasoning. Third, Theological-Religious Interpretation. This used as last alternative to read Quran. Arkoun points out to two essential characteristics of this approach. First, any type of belief-oriented reading falls under the “dogmatic enclosure”. Second, the early monumental works of exegesis contributed to the historical development of “the living tradition”.